Metodologias ativas em diálogo com os quatro pilares da educação: ato responsável para a educação sustentável - Rocha, Meiriele da Silva Rodrigues (2021)
This research aims to analyze the dialogues between active methodologies and the four pillars of education to observe how teaching methodologies are responsible acts that result in quality education and train citizens competent to build a sustainable society. Education plays an important role in the formation of subjects and it needs to adapt to new sociocultural demands, as the different industrial and technological revolutions have changed the labor market and have demanded, every day, new skills and abilities. The methodology adopted in this research is bibliographical and qualitative, as we present a study on dialogism, a constitutive element of language presented by Mikhail Bakhtin and the Bakhtin Circle, to anchor the analysis in the discourses of active methodologies and the four pillars of education. The concepts of dialogue and responsible act underlie the investigation of the dialogical relationships that permeate the thoughts of Brazilian educator Paulo Freire with regard to the meaningful formation of learning, and which can also be observed in the objectives proposed by the Unesco Report that presents the four pillars of education. These pillars are essential for learning, as well as for the proposal of active methodologies. Educational scientists instigate and defend autonomy, curiosity and ethics, in addition to respect for literacy and multiliteracies involved in the knowledge already acquired by students in different sociocultural contexts in which they live. The active methodologies dialogue and respond to the pedagogical proposals developed by Paulo Freire and the pillars of education, but to make them effective in basic education, ethical actions by the teacher are needed. Therefore, the role of the teacher is essential in the construction of knowledge, as it is up to him/her to contribute to the development of citizens and prepare them to act in a society that demands responsiveness and sustainable actions in favor of a more egalitarian world as defined by the goals of the 2030 Agenda. Keywords: Dialogue; responsible act; active methodologies; pillars of education; 2030 Agenda.